Anti-rheumatic colchicine phytochemical exhibits potent antiviral activities against avian and seasonal Influenza A viruses (IAVs) via targeting different stages of IAV replication cycle - Akram Hegazy; Raya Soltane; Ahlam Alasiri; Islam Mostafa; Ahmed M. Metwaly; Ibrahim H. Eissa; Sara H. Mahmoud; Abdou Kamal Allayeh; Noura M. Abo Shama; Ahmed A. Khalil; Ramya S. Barre; Assem Mohamed El-Shazly; et al. (BMC, 2024)
Abstract Background The continuous evolution of drug-resistant influenza viruses highlights the necessity for repurposing naturally-derived and safe phytochemicals with anti-influenza activity as novel broad-spectrum anti-influenza medications. Methods In this study, nitrogenous alkaloids were tested for their viral inhibitory activity against influenza A/H1N1 and A/H5N1 viruses. The cytotoxicity of tested alkaloids on MDCK showed a high safety range (CC50 > 200 µg/ml), permitting the screening for their anti-influenza potential. Results Herein, atropine sulphate, pilocarpine hydrochloride and colchicine displayed anti-H5N1 activities with IC50 values of 2.300, 0.210 and 0.111 µg/ml, respectively. Validation of the IC50 values was further depicted by testing the three highly effective alkaloids, based on their potent IC50 values against seasonal influenza A/H1N1 virus, showing comparable IC50 values of 0.204, 0.637 and 0.326 µg/ml, respectively. Further investigation suggests that colchicine could suppress viral infection by primarily interfering with IAV replication and inhibiting viral adsorption, while atropine sulphate and pilocarpine hydrochloride could directly affect the virus in a cell-free virucidal effect. Interestingly, the in silico molecular docking studies suggest the abilities of atropine, pilocarpine, and colchicine to bind correctly inside the active sites of the neuraminidases of both influenza A/H1N1 and A/H5N1 viruses. The three alkaloids exhibited good binding energies as well as excellent binding modes that were similar to the co-crystallized ligands. On the other hand, consistent with in vitro results, only colchicine could bind correctly against the M2-proton channel of influenza A viruses (IAVs). This might explicate the in vitro antiviral activity of colchicine at the replication stage of the virus replication cycle. Conclusion This study highlighted the anti-influenza efficacy of biologically active alkaloids including colchicine. Therefore, these alkaloids should be further characterized in vivo (preclinical and clinical studies) to be developed as anti-IAV agents.